Thailand's 20 Year Program to Title Rural Land - Burns, Anthony (Washington, DC: World Bank, 2012)
In 1982, because there was increasing pressure on land resources in Thailand, the Department of Lands designed and implemented a 20 year Land Titling Program (LTP) to grant secure tenure to agricultural landholders. The success of the program has been due to a number of factors, including the clear vision for the project, the long-term plan to achieve this vision and the commitment of RTG and key stakeholders to project implementation. There was also a strong policy, legal and institutional framework for land administration in Thailand and a long history of land titling.